Inovasi Media Presentasi Interaktif melalui Pelatihan Pemanfaatan Aplikasi Prezi - Amalia, Dina; Nasyirin, Bagus Khairun; Hana, Shofiyatul (Bahasa Indonesia, 2024)
Innovation in development of interactive presentation media through training in the use of Prezi application offers new potential in designing and delivering Pengabdian kepada Masyarakat (PkM) initiatives an interesting and effective way. This PkM aims to provide knowledge and creative presentation skills for MA Miftahul Huda Bulungan Jepara students through a practical and interactive approach using modern technology use Prezi application. The method for this service activity starts from introduction, implementation, and evaluation through pre-test and post-test questionnaires. Expected output will provide participants with the skills to produce more dynamic and interesting presentations, as well as a deeper understanding of the potential of Prezi's interactive features. PkM Gap Analysis in a holistic approach to developing presentation skills, combining technical aspects of using the Prezi application with increasing participant creativity. This innovation brings a training concept that does not only focus on technical skills, but also seeks a transformation in the way participants organize and present presentation materials through the Prezi application. Results of service obtained a pre-test score of 10% and a post-test score of 60%, an increase in scores showing that the training was successful in increasing effectiveness of presentations and enriching participants' experience through use of Prezi features. Abstrak Inovasi dalam pengembangan media presentasi interaktif melalui pelatihan pemanfaatan aplikasi Prezi menawarkan potensi baru dalam merancang dan menyampaikan inisiatif Pengabdian kepada Masyarakat (PkM) dengan cara yang menarik dan efektif. PkM ini bertujuan untuk memberikan pengetahuan dan ketrampilan presentasi yang kreatif bagi para siswa dan siswi MA Miftahul Huda Bulungan Jepara melalui pendekatan praktis dan interaktif menggunakan teknologi modern berupa aplikasi Prezi. Metode pada kegiatan pengabdian ini dimulai dari pendahuluan, pelaksanaan, dan evaluasi melalui angket pre test dan post test. Luaran yang diharapkan dapat memberikan peserta ketrampilan untuk menghasilkan presentasi yang lebih dinamis dan menarik, serta pemahaman lebih mendalam tentang potensi fitur-fitur interaktif yang dimiliki oleh Prezi. Analisis Gap PkM yaitu terletak pada pendekatan holistik terhadap pengembangan keterampilan presentasi, menggabungkan aspek teknis penggunaan aplikasi Prezi dengan peningkatan kreativitas peserta. Inovasi ini membawa konsep pelatihan yang tidak hanya memfokuskan pada keahlian teknis semata, tetapi juga mengupayakan transformasi dalam cara peserta menyusun dan menyajikan bahan presentasi melalui aplikasi Prezi. Hasil pengabdian diperoleh nilai pre test 10% dan nilai post test 60% kenaikan nilai menunjukkan pelatihan berhasil meningkatkan efektivitas presentasi dan memperkaya pengalaman peserta melalui penggunaan fitur-fitur Prezi.